IMPLEMENTASI BIMBINGAN PERKAWINAN PRA NIKAH DI KUTAI KARTANEGARA KALIMANTAN TIMUR - Miftahurrizki, Miftahurrizki (Realita : Jurnal Bimbingan dan Konseling, 2024)
Pre-marital marriage guidance by the Office of Religious Affairs (KUA) is not just a series of formal meetings, but an integral part of the mental, spiritual, and practical preparation for prospective couples before marriage. This program is responsible for providing comprehensive guidance and insights for those embarking on the journey of life together as husbands and wives. With that said, this research focused on the effectiveness of the materials and approaches used in the guidance, as well as the responses and perceptions of prospective couples, offering a profound view of the crucial role this program plays in marriage preparation. The research employed qualitative methods with a case study approach, utilizing direct observation, interviews with KUA officials, prospective couples attending the guidance, and guidance counselors as data sources. The findings highlighted the significant role of this program in preparing prospective couples holistically. The materials and approaches employed played a pivotal role in their physical, mental, and spiritual readiness for marriage. Positive responses from prospective couples indicated the success of the program, although challenges like program adjustments and continuous evaluation need attention to enhance its future effectiveness. The research underscored the need for ongoing development of marriage guidance programs to make them more beneficial and relevant to prospective couples.